Revocation of Political Rights of The Perpetrators of Criminal Acts of Corruption - Wangga, Maria Silvya E.; Pujiyono, Pujiyono; Arief, Barda Nawawi (Universitas Negeri Semarang, 2019)
The purposes of this paper are to identify and examine the revocation of political rights for corruptors as an extra-ordinary measure. The research showed that law enforcement through penal policies still have shortcomings such as light criminal sentence for perpetrators of criminal acts of corruption as well as lack of awareness among judges to apply the additional sentence of fixed-time revocation of rights. Penal law enforcement requires integral and sustainable policies through non-penal policies (prevention). Preventive efforts should be responsive to the demands of the community at large for officials who are clean, honest and who have integrity. Non-penal law shall be enforced through the concept of developing smart and integrity-based politics.